Antioxidant Secondary Metabolites in Cereals: Potential Involvement in Resistance to Fusarium and Mycotoxin Accumulation - Atanasova-Penichon, Vessela; Barreau, Christian; Richard-Forget, Florence (Frontiers in Microbiology, 2016)
Gibberella and Fusarium Ear Rot and Fusarium Head Blight are major diseases affecting European cereals. These diseases are mainly caused by fungi of the Fusarium genus, primarily Fusarium graminearum and Fusarium verticillioides. These Fusarium species pose a serious threat to food safety because of their ability to produce a wide range of mycotoxins, including type B trichothecenes and fumonisins. Many factors such as environmental, agronomic or genetic ones may contribute to high levels of accumulation of mycotoxins in the grain and there is an urgent need to implement efficient and sustainable management strategies to reduce mycotoxin contamination. Actually, fungicides are not fully efficient to control the mycotoxin risk. In addition, because of harmful effects on human health and environment, their use should be seriously restricted in the near future. To durably solve the problem of mycotoxin accumulation, the breeding of tolerant genotypes is one of the most promising strategies for cereals. A deeper understanding of the molecular mechanisms of plant resistance to both Fusarium and mycotoxin contamination will shed light on plant-pathogen interactions and provide relevant information for improving breeding programs. Resistance to Fusarium depends on the plant ability in preventing initial infection and containing the development of the toxigenic fungi while resistance to mycotoxin contamination is also related to the capacity of plant tissues in reducing mycotoxin accumulation. This capacity can result from two mechanisms: metabolic transformation of the toxin into less toxic compounds and inhibition of toxin biosynthesis. This last mechanism involves host metabolites able to interfere with mycotoxin biosynthesis. This review aims at gathering the latest scientific advances that support the contribution of grain antioxidant secondary metabolites to the mechanisms of plant resistance to Fusarium and mycotoxin accumulation.